Pengaruh Locus of Control Dan Kepuasan Kerja Terhadap Kinerja Karyawan Dengan Self Esteem Sebagai Variabel Moderating - Divani Tara; Bella Pavita Yolanda; Sri Wulandari (Pusat Riset Manajemen Dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia, 2023)
At PT. Pins Indonesia based on the results of surveys and interviews found several problems that occurred at PT. Pins Indonesia, the results obtained relating to work motivation, job satisfaction and length of work occurred, among others, as seen from employee performance influenced by several employees who felt that there was still a lack of employees to complete quite a lot of work and also the existence of employee negligence when providing services, employees also undisciplined, which is one description of an employee's performance. The purpose of this article is to find out how location and job satisfaction influence performance with self-esteem as a moderating variable at PT Pins Indonesia. This research uses quantitative methods with a descriptive approach. The test results show that the locus variable of control has an influence on performance. The research results show that the job satisfaction variable has an influence on employee performance. Meanwhile, the results of the variables locus of control and job satisfaction are not mediated by self-esteem. As a result of self-esteem which cannot mediate location and job satisfaction, there is no encouragement for employees to be confident in their abilities.